LEADERSHIP MANAGEMENT OF SCHOOL PRINCIPALS, TEACHER PROFESSIONALISM AND COMMUNITY PARTICIPATION IN IMPROVING THE QUALITY OF EDUCATION AT SMK IT MADANI BAROS, SUKABUMI CITY - Raudatul Janah; Mulyawan Safwandy Nugraha (Media Inovasi Pendidikan dan Publikasi, 2023)
Based on the whole description of the principal's management, teachers' professionalism and the community's participation in improving the quality of teaching in this school, it can be concluded from the research results that the educational program organized by the school organization is basically very successful. it is difficult to achieve if the opinions of the principal, teachers and the community about the real meaning of education and the implementation of the educational process in schools are not harmonized. Therefore, school leaders in this case the principal, teachers and the community must work in an integrated manner to achieve each educational goal. Forming the next generation of quality in terms of knowledge, skills and attitudes. When we talk about education, the first thing that comes to mind is